Hegemonic masculinity: contingencies related to health deficit self-care in men - Sousa, Alex da Silva (Perspectivas em Análise do Comportamento, 2022)
Men’s health is considered a significant public health problem and because it poses a question of social impact, addressed in research or matrices of different scientific sciences. According to the gender paradigm, one of the most recognized theoretical models on this issue, men present worrying health indicators because they seek to correspond to the impositions of the male gender role. The objective of this work is to conceptualize masculinity in a behavioral frame, with emphasis on the hegemonic model. Secondly, we seek to hypothesize some contingencies related to the difficulty of self-care for health, attributed to men. Methodologically, this study is a conceptual analysis built from the examination of fundamental literatures in approaching this problem. It is concluded that hegemonic masculinity can be interpreted as a cultural practice, maintained by contingencies existing in societies in which patriarchy is still intense, composed of control agencies. Beliefs, values and perceptions about what it means to be a man are a context, probably working like rules, that makes risky behavior more likely.